2022
DOI: 10.3389/fpsyg.2022.926534
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ambient air pollution on outdoor employees’ performance: Mediating role of anxiety

Abstract: This paper aims to examine the direct and indirect impact of ambient air pollution (AAP) on employees’ performance. This study has used cross sectional survey design to collect the data from the outdoor employees of the pharmaceutical industry of Pakistan. The data were collected in time lags from 299. Partial least squares- structural equation modeling (PLS-SEM) approach was applied to analyze the data. The results show that AAP has a significant negative impact on the employees’ performance, and anxiety part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 86 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…suggested that air pollution may negatively impact employees’ performance. Authors point out that anxiety is the mediator in that correlation ( 30 ). Nonetheless, the sample size was relatively small (299 participants) and comprised only pharmaceutical workers.…”
Section: Air Pollutionmentioning
confidence: 99%
“…suggested that air pollution may negatively impact employees’ performance. Authors point out that anxiety is the mediator in that correlation ( 30 ). Nonetheless, the sample size was relatively small (299 participants) and comprised only pharmaceutical workers.…”
Section: Air Pollutionmentioning
confidence: 99%
“…Effective green product development capabilities can facilitate the transition of businesses and economies toward environmental sustainability. Through technological green initiatives, organizations may gain ecological benefits and a competitive advantage in the market by creating green products (Bari et al, 2022; Singjai et al, 2018). By incorporating Industry 4.0's environment‐friendly technology capability, companies can commit to sustainability by regularly evaluating and improving their environmental impact using real‐time data to boost their GDC.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the study only considered open window ventilation frequency; however, ventilation time, ventilation location, and other types of ventilation (e.g., air conditioning) were not included and need further research; for example, it is needed to explore the impact of different ventilation durations or time periods or specific ventilation location (living room or/and kitchen) on depression and anxiety. Third, pollutants from the outdoor environment may also affect depression and anxiety symptoms in older people [51,52], and ventilation may cause pollutants that were originally outside to enter the house instead. Further study is needed to control for outdoor environmental factor to assess the true association between ventilation and health.…”
mentioning
confidence: 99%